PERTUMBUHAN SEMAI MAHONI (Swietenia mahagoni (L) Jacq) PADA BERBAGAI TAKARAN PUPUK MAJEMUK NITROGEN POSPAT KALIUM - Asriani, .; Umar, Husain; Rahmawati, . (Jurnal Warta Rimba, 2018)
Mahogany has fast growth and produces hard mahogany used for furniture. An important factor determining the success of mahogany planting is the availability of quality seeds. For that, the things to note are the availability of nutrients and water sufficient for the growth of seedlings. In the fulfillment of seedling needs, used NPK compound fertilizer. The purpose of this research is to know the growth of mahogany seedlings at various doses of NPK compound fertilizer. The research method used was Randomized Complete Design (RAL) consisting of four treatments, namely P0 = Soil (control), P1 = Soil + NPK fertilizer with dose (5 g), P2 = Soil + NPK fertilizer with dose (10 g) and P3 = Soil + NPK fertilizer with dose (15 g). Each treatment is repeated five times so that it needs 20 seeds of samples, each polybag is one mahogany. The data obtained based on the observed results were analyzed by using the analysis of the variety and treatment that had real or very real effect tested further by using the Honest Different Test (BNJ) at the level (5%). The result of this research shows that the dosage of NPK fertilizer has significant effect on all parameters, that is the height of seedlings, the stem diameter, the leaf number, the wet weight of the seedlings and the dry weight of the seedlings. Soil treatment + NPK fertilizer with dose (15 g) (P3) gave the best influence to the growth of mahogany seedlings in almost all observed parameters, where the average height increase of seedlings, ie 2.40 mm, stem diameter increase, ie 1.21 cm, the increase of leaf number, that is 3.03 strands, wet weight of seedlings, that is 2.75 g and dry weight of seedlings is 2.15 gr.